The Hesitant Confucian-Centered Catholic Believers of the Ming and Qing Dynasties: A Review of Heaven and Confucianism Are Essentially the Same: A Study on the New Orthodoxy Thought of Confucian Catholic Believers in the Late Ming and Early Qing Periods (2017) - CHANG , Kai (Journal of Research for Christianity in China (JRCC), 2025)
No Abstract